Hubungan antara Perubahan Organisasi, Budaya Organisasi, Kepemimpinan Transformasional, dan Kinerja Karyawan pada PT Pancaputra Mitratama Mandiri - Shabrina, Safira (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research tries to find the relationship between organizational change, organizational culture, transformational leadership, and employee performance at PT Pancaputra Mitratama Mandiri. This research is using a quantitative approach. The population in this study are 32 employees at PT Pancaputra Mitratama Mandiri. Data are running using software SmartPLS, which uses SEM and PLS. The results in this research are (1) Transformational leadership has an insignificant impact on employee performance, (2) transformational leadership has a significant impact on organizational change, (3) transformational leadership has a significant impact on organizational culture, (4) organizational change has an insignificant impact on employee performance, (5) organizational culture has an insignificant impact on employee performance, (6) organizational change has a significant impact on organizational culture, (7) transformational leadership on employee performance has not indirect impact by organizational culture, (8) transformational leadership on employee performance has not indirect impact by organizational change, and (9) organizational change on employee performance has not indirect impact by organizational culture.